Barriers to decolonising educational partnerships in global health - John Kulesa; Nana Afua Brantuo (BMJ Global Health)
Global health partnerships between high-income countries and low/middle-income countries can mirror colonial relationships. The growing call to advance global health equity therefore involves decolonising global health partnerships and outreach. Through decolonisation, local and international global health partners recognise non-western forms of knowledge and authority, acknowledge discrimination and disrupt colonial structures and legacies that influence access to healthcare.Despite these well-described aims, the ideal implementation process for decolonising global health remains ill-defined. This ambiguity exists, in part, because partners face barriers to adopting a decolonised perspective. Such barriers include overemphasis on intercountry relationships, implicit hierarchies perpetuated by educational interventions and ethical dilemmas in global health work.In this article, we explore the historical entanglement of education, health and colonialism. We then use this history as context to identify barriers that arise when decolonising contemporary educational global health partnerships. Finally, we offer global health partners strategies to address these challenges.